Functioning of diminutive nouns in the texts of historical spivanki-chronicles (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the peculiarities of functioning, the specifity of semantics and word-formative structure of diminutive nouns used in spivanki-chronicles with historical basis; analyzes derivatives formed by means of joining seventeen suffixes to motivating base; defines the importance and necessity of their usage in folklore text.
Keywords: deminuty; wordforming structure; stylistic feature